The Federal Reserve's evolving monetary policy implementation framework: 1914-1923 - Benjamin Chabot (Federal Reserve Bank of Chicago, 2017)
The Federal Reserve has relied upon a number of different monetary policy implementation frameworks throughout its history. This paper describes the original implementation framework that evolved between 1914 and 1923 in response to new policy objectives and changing market conditions.
Keywords: 330